Respuesta :

d - 20 is = to d + (-20)
20 - d is = to 20 + (-d)
-d + 20 is not the same as
d + (-20).

Answer:

Because given expression are not same.

Step-by-step explanation:

We are given that an  expression

d minus 20

We are given that the given algebraic expression is not equivalent to 20 minus d why.

d minus 20=[tex]d-20[/tex]

20 minus d=[tex]20-d=-(d-20)[/tex]

Hence,20 minus d is negative times of d minus 20.

Therefore, the given expression are not equivalent because given expression are not same.